Development of the four-stage thermoacoustic engine operating in the low-temperature range of self-starting and on Stirling cycle - Kaiyrly, Dias; Sarsikeyev, Yermek; Mekhtiyev, Ali; Ansapov, Arystanbek; Akmaganbetova, Zhanar (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to improvement a four-stage thermoacoustic motor with a rectangular cross-section for operation in the low-temperature range of self-starting, operating on the Stirling thermal cycle, with the effect of a standing sound wave. In carrying out the research tasks, mathematical modeling methods were used to calculate technological parameters, and a prototype thermoacoustic engine with self-starting in the low-temperature range with four stages was created. Research results. It was determined that the obtained sample differs significantly from its analogues, indicating that the operating nature of the developed thermoacoustic engine differs from existing traditional ones. The hot heat exchanger is capable of operating in the range from 60 to 100 degrees Celsius. A cold heat exchanger, on the other hand, operates in the range of 30 to 50 degrees Celsius heat exchanger. On the other hand, it was determined that the engine power reaches a value of 115 Watts at 100 degrees Celsius, and the frequency varies from 50.4 to 62.3 Hz. The disadvantage is the low generation capacity, as a result of which this system can only be used as a cogeneration plant. The results can be used to create cogeneration energy sources for autonomous consumers.